Role of Vaccum Dressings In Open Wounds of Pilonidal Sinus: Vaccum Dressings in Open Wounds of Pilonidal Sinus - Faheem, Komal; Zaheer, Farhan; Faizan, Muhammad; Jawaid, Bushra; Shahab, Hassan; Salman, Sumbla; Bin Shoaib, Umer; Siddiqui, Sarush Ahmed; Hasan, Mohammad (Pakistan Journal of Health Sciences, 2023)
Pilonidal sinus is an acute suppurative condition occurring beneath the sacrococcygeal area presenting as an abscess acutely while as intermittent discharge in its chronic form. Objective: To determine the role of NPWT in the management of pilonidal sinus in a tertiary care hospital in Karachi, Pakistan over 6 months. Methods: 50 patients were divided into two groups; control and NPWT. It was an open-label randomized trial. The patients in the control group were being managed by wet dressing compared to the NPWT group where VAC therapy was used for wound healing. Both groups were followed for 14 days. Healing was measured by VAS score, wound size, and number of complications. Results: Wound size post-operatively was measured in both groups and was 36.33 squared centimeters in the control group with 30. 97 squared centimeters in the intervention group showed no statistical significance. On the 14th day of the trial, the wound size was compared again and in the control group, the size was found to be 24.4 cm2 and 14.9 cm2 in the intervention group. However, no statistical significance was shown. On the visual analog scale for pain after 14 days, both groups demonstrated a steep decline falling to nearly 1.5 from 9 on the first postoperative day however showing no significant difference across the two groups. Conclusions: There was no significant difference between the two methods and similar time was required in both groups before resuming daily life activities.